Validitas E-modul Fisika Energi Alternatif dan Pemanasan Global Kelas X Berbasis Model Pembelajaran Berbasis Masalah Terintegrasi Pembelajaran Abad 21 - Korry Nilyani; Ratnawulan (Postgraduate, University of Mataram, 2023)
This research aims to reveal the level of validity of class prepared based on the syntax of the problem based learning model and integrated with the four 21st century skills, namely, collaboration skills, critical thinking skills, creative thinking skills and communication skills. This research is research and development using the Plomp model. The instrument used was a questionnaire and the data was analyzed descriptively based on the validation score sheet. Products are validated by experts. The observation results were analyzed using the Aiken V formula. The results of the analysis showed the average value of Aiken's V was 0.97. The validity results show that the physics e-module meets the valid criteria. These findings indicate that the physics e-module on alternative energy and global warming material, based on problem based learning integrated with 21st century learning, is suitable for use.